Biodiversity informatics, Biota/FAPESP and the future a personal view (Biota Neotropica, 2001)
This paper explores the development of the FAPESP/Biota project from the view of an external adviser. It explores the implementation of advice received and the development of the project through the first three years, and provides some views on future directions for the project.